Global Gene Expression in Staphylococcus aureus Biofilms - Beenken, Karen E. (American Society for Microbiology, 2004)
We previously demonstrated that mutation of the staphylococcal accessory regulator (sarA) in a clinical isolate of Staphylococcus aureus (UAMS-1) results in an impaired capacity to form a biofilm in vitro (K. E. Beenken, J. S. Blevins, and M. S. Smeltzer, Infect. Immun. 71:4206-4211, 2003). In this report, we used a murine model of catheter-based biofilm formation to demonstrate that a UAMS-1 sarA mutant also has a reduced capacity to form a biofilm in vivo. Surprisingly, mutation of the UAMS-1 ica locus had little impact on biofilm formation in vitro or in vivo. In an effort to identify additional loci that might be relevant to biofilm formation and/or the adaptive response required for persistence of S. aureus within a biofilm, we isolated total cellular RNA from UAMS-1 harvested from a biofilm grown in a flow cell and compared the transcriptional profile of this RNA to RNA isolated from both exponential- and stationary-phase planktonic cultures. Comparisons were done using a custom-made Affymetrix GeneChip representing the genomic complement of six strains of S. aureus (COL, N315, Mu50, NCTC 8325, EMRSA-16 [strain 252], and MSSA-476). The results confirm that the sessile lifestyle associated with persistence within a biofilm is distinct by comparison to the lifestyles of both the exponential and postexponential phases of planktonic culture. Indeed, we identified 48 genes in which expression was induced at least twofold in biofilms over expression under both planktonic conditions. Similarly, we identified 84 genes in which expression was repressed by a factor of at least 2 compared to expression under both planktonic conditions. A primary theme that emerged from the analysis of these genes is that persistence within a biofilm requires an adaptive response that limits the deleterious effects of the reduced pH associated with anaerobic growth conditions.